Integrating Makassar Tourism Information Systems in Support of Smart Tourism City - Aliah, Nurul (PINISI Discretion Review, 2025)
The rapid advancement of digital technology has transformed the tourism sector into a data-driven ecosystem that demands system integration and collaborative governance. This study aims to analyze the role of tourism information system integration in supporting Makassar’s transition toward a Smart Tourism City. Employing a mixed-method sequential explanatory approach, the research combines quantitative analysis through a structured questionnaire distributed to 134 stakeholders including government officials, tourism industry actors, and creative communities with qualitative exploration through observation and document analysis of the Makassar Tourism Master Plan (RIPPAR 2022–2037). Quantitative results indicate that digital infrastructure (β = 0.334), system integration (β = 0.297), and digital utilization (β = 0.291) significantly influence smart tourism performance (R² = 0.734, p < 0.05). Qualitative findings support these results, revealing that while digital facilities and community participation are strong, institutional data integration remains partial. The overall Digital Tourism Integration Index (IIDK) reached 77.4%, classifying Makassar as “digitally ready but partially integrated.” The study concludes that the success of a smart tourism city depends not only on technological readiness but also on the alignment of governance structures and participatory collaboration across sectors. Practically, this research recommends establishing a centralized digital tourism data hub and strengthening inter-agency coordination to achieve full interoperability and sustainable digital governance. The findings provide both empirical insight and policy implications for urban digital transformation, particularly for developing cities aiming to advance toward sustainable smart tourism ecosystems.